(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Researchers, international traders, and politicians necessitate a common interactive language to deal and keep their work secure. Using a direct language translator enables customers to deal with others, each one uses his own mother languages. This machine fulfills security, and confidence. The translation machines include in their memories, databases for synonyms, and vocabularies for the bi- languages. This system may be used in teleconferences and international political committees. This paper presents a modular system that translates Arabic toÂ English and English to Arabic (AE-EA) via a real time interactive system. This necessitates standard references for Speech to Text (ST) , Text to Speech (TS) and Text to Text Translators (TTT). The paper test statistically, the accuracy of transformation, it gave encourageous results. Â